2023
DOI: 10.1186/s12906-023-03966-1
|View full text |Cite
|
Sign up to set email alerts
|

Flowering phenophases influence the antibacterial and anti-biofilm effects of Thymus vulgaris L. essential oil

Abstract: Background Essential oils are becoming increasingly popular in medicinal applications because of their antimicrobial effect. Thymus vulgaris L. (Lamiaceae) is a well-known and widely cultivated medicinal plant, which is used as a remedy for cold, cough and gastrointestinal symptoms. Essential oil content of thyme is responsible for its antimicrobial activity, however, it has been reported that the chemical composition of essential oils influences its biological activity. In order to explore flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Thy possesses both antioxidant and antibacterial activities and is one of the main components in essential oils such as oregano, thyme, and winter peppermint. Thymus vulgar is essential oil, for instance, has been found to exhibit antibacterial activity against various Gram-negative and Gram-positive bacteria by inducing intracellular glycans and protein molecule leakage, altering membrane permeability, and disrupting phospholipid bilayers, ultimately leading to microbial death (Galovicova et al, 2021;Bako et al, 2023).…”
Section: Reduction Rate and Growth Curve Of Bacteriamentioning
confidence: 99%
“…Thy possesses both antioxidant and antibacterial activities and is one of the main components in essential oils such as oregano, thyme, and winter peppermint. Thymus vulgar is essential oil, for instance, has been found to exhibit antibacterial activity against various Gram-negative and Gram-positive bacteria by inducing intracellular glycans and protein molecule leakage, altering membrane permeability, and disrupting phospholipid bilayers, ultimately leading to microbial death (Galovicova et al, 2021;Bako et al, 2023).…”
Section: Reduction Rate and Growth Curve Of Bacteriamentioning
confidence: 99%
“…The strongest antibacterial and anti-biofilm activity was shown in thyme oil obtained through distillation of fresh plant material gathered at the onset of the flowering period. This oil demonstrated efficacy against many microorganisms, including P. aeruginosa ( Bakó et al, 2023 ). Finally, a further study on the anti-biofilm properties of thymol found that this powerful plant compound is mostly present in log (30.28%) and stationary phase (20.89%) extracts.…”
Section: Thymolmentioning
confidence: 99%
“…Among the plant essential oils, immortelle (Helichrysum italicum), Origanum majorana, thyme and citrus showed valuable biofilm inhibition activity against P. aeruginosa and H. influenzae [51][52][53][54].…”
Section: Biofilm Inhibitorsmentioning
confidence: 99%
“…Dioon spinulosum extract P. aeruginosa [49] Plant-derived triterpenes (analogs of oleanolic acid) P. aeruginosa, B. cenocepacia [50] Plant essential oils P. aeruginosa, H. influenzae [51][52][53][54] Ceragenins (CSAs) A. xylosoxidans [55] Metalloproteases from stony coral S. maltophilia [56] Vitamin C S. maltophilia [57] Allium stipitatum extract S. maltophilia [58] Glycosyl hydrolases PslG from P. fluorescens Pseudomonas strains…”
Section: Biofilm Inhibitors Bacteria Referencementioning
confidence: 99%